Buddhism and Science in the Mirror of Language - Cho, Francisca (Religions: A Scholarly Journal, 2014)
From the very beginning of the European encounter with Buddhism, both Asian and western commentators have argued that Buddhism is compatible with Science, at the risk of producing a naturalistic interpretation of the teaching of the Buddha. If the dialogue between Buddhism and science is to be substantial, then it is critical to understand Buddhism better than many presently do. Better understanding means assessing the conflict between religion and science from a Buddhist perspective, rather than reducing Buddhism to the mere object of scientific validation or refutation. Buddhist assumptions are different from western ones and its major teachings—such as karma—are best not shoehorned into foreign philosophical frameworks like Cartesian mind/body dualism. In this paper, the author focuses on one salient example. The arc of Buddhist tradition probes and questions the belief that human language is able to articulate timeless and universal truths. If this skepticism about the capacity of language is justified, then it has direct significance for the modern western tension between religion and science because this conflict centers on whose propositions and narratives about the universe are correct. If we take Buddhism seriously, one must consider the possibility that neither religious nor scientific discourse can claim definitive knowledge, and that even a combination of the two is not adequate.